Using Augmented Reality with Older Adults in the Community to Select Design Features for an Age-Friendly Park: A Pilot Study - Edgar R. Vieira; Fernanda Civitella; Jorge Carreno; Miburge G. Junior; Cesar F. Amorim; Newton D’Souza; Ebru Ozer; Francisco Ortega; Jansen A. Estrázulas (Journal of Aging Research)
Sedentary behavior is prevalent in older adults. Older adults often underutilize public parks for exercising because the parks do not support their needs and preferences. Engaging older adults on the redesign of parks may help promote active lifestyles. The objectives of this pilot study were to evaluate (1) the effects of wearing augmented reality (AR) and virtual reality (VR) glasses on balance; (2) the effects of different virtual walls separating the walking trail from the roadway on older adults’ gait, and (3) the preferences of the participants regarding wall design and other features. The participants were ten older adults (68 ± 5 years) who lived within two miles from the park. Balance and gait were assessed using a force plate and an instrumented mat. It was feasible to use AR with older adults in the park to evaluate features for redesign. Motion sickness was not an issue when using AR glasses, but balance was affected when wearing VR goggles. The area of postural sway increased approximately 25% when wearing AR glasses, and it increased by close to 70% when wearing VR goggles compared to no glasses. This difference is clinically relevant; however, we did not have enough power to identify the differences as statistically significant because of the small sample size and large variability. Different walls did not significantly affect the participants’ gait either because they did not alter the way they walked or because the holograms were insufficiently realistic to cause changes. The participants preferred a transparent wall rather than tall or short solid walls to separate the park from the roadway.